Characterization and genesis mechanism of dolomite from Xike 1 well, Xisha Islands—constraints from Mg isotopes - Yazeng, Ma; Heping, Fu; Hong, Xu; Zuozhen, Han; Jinxiong, Luo; Chao, Han (Frontiers in Earth Science, 2025)
Dolomite is widely developed in the Xisha Islands, and there are numerous views on its genesis, with no uniform understanding at present. In this paper, the formation mechanism of dolomite of the Xike 1 well in the Xisha Islands was investigated on the basis of the petrological and geochemical characterization of core samples using experiments such as thin section identification, cathodoluminescence, scanning electron microscopy, electron microprobe, X-ray diffraction, and Mg isotope testing. The results show that (1) most of the dolomite is distributed along the weathering exposure surface with a residual structure. Dolomite without residual structures has a fog-centered bright edge with straight authomorphism or semi-authomorphism, curved surface dominated, and the degree of authomorphism controlled by the growth space; (2) the overall ordering of dolomite in the whole well is low, with an average value of 0.53, and there is little difference in ordering at different depths, the Mn and Fe contents of middle- and shallow-depth dolomites are generally low, and cathodoluminescence is not obvious; for the deep layers, the Mn and Fe contents increased by hydrothermal action, and bright yellow and orange cathodoluminescent bands were formed; (3) changes in the Mg isotopic composition of dolomite along the stratigraphic sequence of the profile are generally consistent with changes in the depositional cycle. Based on the spatially varying trajectories of δ26Mg isotope profile sequences, the results indicate the presence of evaporative lagoon infiltration reflux, mixed water, and geothermally driven hydrothermal dolomitization mechanisms since reef formation.